Lessons from black pepper: piperine and derivatives thereof. (1st February 2016) - Chavarria, D.; Silva, T.; Magalhães e Silva, D.; Remião, F.; Borges, F.
ABSTRACT: Introduction : Piperine is a simple and pungent alkaloid found in the seeds of black pepper ( Piper nigrum ). Following its isolation and full characterization, the biological properties of piperine have been extensively studied, and piperine-like derivatives have shown an interesting range of pharmacological activities. In this context, significant advances have been made in the discovery of new chemical entities based on the piperine scaffold endowed with therapeutic potential. Areas covered : The aim of this review is to provide a thorough inquiry on the therapeutic potential of piperine and related derivatives. It provides an overview of recent developments in patented processes and applications thereof between 2000 and 2015. Expert opinion : Cumulative evidence shows that piperine is currently paving its way to become a privileged scaffold for the development of bioactive compounds with therapeutic application in multiple human diseases. In particular, piperine derivatives were shown to modulate the activity of several targets related to neurological disorders, including epilepsy, Parkinson's disease, depression and pain related disorders. Moreover, the efflux pump inhibitory ability of piperine and its analogues tackles important drug resistance mechanisms and may improve the clinical efficacy of antibiotic and anticancer drugs. Although the use of piperine as a scaffold for bioactive compounds is still in its early stages, the continuous exploration of this structure may lead to remarkable advances in drug discovery programs.